The Manchester–Oxford Foot Questionnaire (MOXFQ): Development and validation of a summary index score. Issue 4 (April 2013) - Morley, D.; Jenkinson, C.; Doll, H.; Lavis, G.; Sharp, R.; Cooke, P.; Dawson, J.
Abstract : Objectives: The Manchester–Oxford Foot Questionnaire (MOXFQ) is a validated 16-item, patient-reported outcome measure for evaluating outcomes of foot or ankle surgery. The original development of the instrument identified three domains. This present study examined whether the three domains could legitimately be summed to provide a single summary index score. Methods: The MOXFQ and Short-Form (SF)-36 were administered to 671 patients before surgery of the foot or ankle. Data from the three domains of the MOXFQ (pain, walking/standing and social interaction) were subjected to higher order factor analysis. Reliability and validity of the summary index score was assessed. Results: The mean age of the participants was 52.8 years (sd 15.68; 18 to 89). Higher order principle components factor analysis produced one factor, accounting for 74.7% of the variance. The newly derived single index score was found to be internally reliable (α = 0.93) and valid, achieving at least moderate correlations (r ≥ 0.5, p < 0.001) with related (pain/function) domains of the SF-36. Conclusions: Analyses indicated that data from the MOXFQ can be presented in summary form. The MOXFQ summary index score (MOXFQ-Index) provides an overall indication of the outcomes of foot and ankle surgery. Furthermore, the single index reduces the number of statistical comparisons, and hence the role of chance, when exploring MOXFQ data.